2014
DOI: 10.1016/j.egja.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Safety and vasopressor effect of rosuvastatin in septic patients

Abstract: Background: Statins anti-inflammatory and antioxidant properties improve vascular function in septic patients. The aim of this prospective study was to assess vasopressor effect and safety of rosuvastatin therapy in septic patient. Methods: One hundred and eight patients admitted to intensive care unit (ICU) with suspected or confirmed infection plus at least 2 systemic inflammatory response syndrome criteria were included in this prospective double-blinded randomized two groups' parallel study. Group R receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
1
8
1
Order By: Relevance
“…Significant earlier hemodynamic stabilization at both lower dose and shorter duration of vasopressor was reportedly achieved with rosuvastatin in the study by El Gendy and Elsharnouby. [ 15 ] In contrast to this, we did not observe any significant difference in either hemodynamics or vasopressor dose or vasopressor-free days between statin and placebo group. The reasons for these differences could be multifactorial.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Significant earlier hemodynamic stabilization at both lower dose and shorter duration of vasopressor was reportedly achieved with rosuvastatin in the study by El Gendy and Elsharnouby. [ 15 ] In contrast to this, we did not observe any significant difference in either hemodynamics or vasopressor dose or vasopressor-free days between statin and placebo group. The reasons for these differences could be multifactorial.…”
Section: Discussioncontrasting
confidence: 92%
“…Varying proportions (0%–79%) of septic shock patients have been included in previous RCTs. [ 10 11 12 13 14 15 16 ] The present RCT, an exclusive cohort of septic shock patients using atorvastatin (higher dose albeit shorter course), is in concordance with previous RCTs.…”
Section: Discussionsupporting
confidence: 89%
“…Of the 9 trials, patients in 4 trials received atorvastatin, [ 14 , 15 , 19 , 22 ] patients in 3 trials received simvastatin, [ 16 18 ] and patients in 2 trials received rosuvastatin. [ 20 , 21 ] Four trials reported in-hospital mortality, [ 14 , 17 , 20 , 21 ] 2 trials reported 28-day mortality, [ 19 , 22 ] and 3 trials reported both as outcome of interest. [ 15 , 16 , 18 ] Detailed characteristics of the included studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for exclusion of full text records are detailed in figure 1. Authors for three studies were contacted to determine eligibility because the limited information in the publication did not allow for definitive assessment [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…We mitigated against this by conducting a comprehensive search of both electronic and non-electronic based repositories. Nonetheless, there were three trials that may potentially have provided additional data but that we were forced to exclude due to lack of further information from study authors, although given that the sample sizes in these studies were small it is unlikely to have materially affected the results [26][27][28].…”
Section: Discussionmentioning
confidence: 99%